2014
DOI: 10.1590/s0103-84782014005000002
|View full text |Cite
|
Sign up to set email alerts
|

Decomposição da fitomassa de plantas de cobertura e liberação de nitrogênio em função da quantidade de resíduos aportada ao solo sob sistema plantio direto

Abstract: Decomposição da fi tomassa de plantas de cobertura e liberação de nitrogênio em função da quantidade de resíduos... Ciência Rural, v.44, n.5, mai, 2014. 801Decomposição da fi tomassa de plantas de cobertura e liberação de nitrogênio em função da quantidade de resíduos aportada ao solo sob sistema plantio direto Fitomass decomposition and nitrogen release of cover crops in function of the level of residue input to soil under no-tillage system ABSTRACT The no-tillage system success relies on higher addition of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 20 publications
1
26
1
4
Order By: Relevance
“…According to Aita, Giacomini, and Ceretta (2014), crop residues with a high C/N ratio are decomposed more slowly. Acosta, Amado, Silva, Santi, and Weber (2014), studying cover crops decomposition, concluded that the decomposition process is regulated by the C/N ratio of the straw.…”
Section: Half-life Of the Dry Mass And Nutrients In The Cover Cropsmentioning
confidence: 99%
“…According to Aita, Giacomini, and Ceretta (2014), crop residues with a high C/N ratio are decomposed more slowly. Acosta, Amado, Silva, Santi, and Weber (2014), studying cover crops decomposition, concluded that the decomposition process is regulated by the C/N ratio of the straw.…”
Section: Half-life Of the Dry Mass And Nutrients In The Cover Cropsmentioning
confidence: 99%
“…Straw is an important nutrient reservoir, which can be gradually, quickly, or even intensely made available (Rosolem et al, 2003). This leach is influenced by the activity of microorganisms found in the soil, by their quality (carbon/nitrogen (C/N) ratio) and amount, by the weather conditions -with emphasis on temperature and rainfall -and by the contact of straw with soil (Acosta et al, 2014). Nutrients leached by the straw, mainly potassium (K) -which presents short half-time life -are important to nurture the subsequent culture.…”
Section: Introductionmentioning
confidence: 99%
“…The grain yield in 2015 adjusted to the quadratic function for doses in the treatments with and without inoculation with A. brasilense, with a positive response up to 142 and 134 kg ha -1 of N, respectively. The N doses mentioned above to obtain the maximum yield of grains were high, because the wheat was cultivated on the maize stover, that is, part of the N that was applied could have been used by immobilized decomposers and/ or mineralizing soil microorganisms (ACOSTA et al, 2014), since the higher the C/N ratio of the stover, the longer the N release time of the vegetal residue, and consequently N demand will be higher for the mineral fertilizer. Means followed by the same letters, in the column, do not differ among themselves by the Tukey's test at 5% probability.…”
Section: Productivity Of Wheat Grainsmentioning
confidence: 99%